IMPROVING THE SKILLS OF WRITING ARGUMENTATIVE PARAGRAPH THROUGH THE JURISPUDENTIAL INQUIRY LEARNING MODEL IN CLASS X STUDENTS - Aldi Aldi; Sitti Rabiah; Nurfathana Mazhud (Citra Dharma Cindekia, 2022)
This study aims to describe the results of increasing skills in writing argumentative paragraphs through the jurisprudential inquiry method for class X MIPA 1 students at SMA Negeri 16 Makassar. This research is a type of Classroom Action Research (CAR). The research sample was all students of class X MIPA 1 while the population for this study were all students of SMA Negeri 16 Makassar. Data collection techniques used student observation sheets and the results of students' argumentative paragraph writing skills. Research data were analyzed using qualitative analysis and quantitative analysis. The results showed that there was an increase in student learning outcomes for each cycle from pre-cycle, cycle I, to cycle II. Based on the average learning outcomes, in each cycle there has been an increase, which in the pre-cycle reached a value of 67, the first cycle reached 78, and the second cycle reached 84. Based on the percentage of the number of completed students, it also experienced an increase in each cycle, which in the pre-cycle the number of students who passed reached only 33%, in cycle I reached 44%, and cycle II reached 86%. It can be concluded that the jurisprudential inquiry learning model was successful in increasing students' skills in writing argumentative paragraphs for class X MIPA 1 students at SMA Negeri 16 Makassar.